A novel technique for the percutaneous removal of tricuspid valve vegetations utilizing the Inari Flowtriever System. Issue 2 (1st June 2022) - Becker, Matthew C.; Reddy, Siddarth; Miccio, Brendan; Pappas, Orestis
Abstract: Right‐sided infective endocarditis is a common entity for which surgical intervention is frequently high‐risk. Considering its invasive nature, potential complications, and challenging patient population, a less invasive endovascular option is desirable. The previous series have demonstrated the feasibility of percutaneous therapy for tricuspid valve (TV) vegetation utilizing a filter‐based bypass circuit. However, the limited availability of a specialized team, resources, procedural complexity, and large bore sheath size restrict the broad adoption of this technique. The Inari FlowTriever System (Inari Medical) is an endovascular, catheter‐based, aspiration, and mechanical thrombectomy system indicated for the removal of large‐volume venous thrombus and pulmonary emboli. Independent of anesthesia, perfusion, or advanced imaging, this device's characteristics uniquely improve the operator's ability to safely remove unwanted debris from complex anatomy. This report describes the first, utilization of the Inari FlowTriever System for the removal of massive and inoperable TV vegetation.